76P Real-world data analysis of PD-L1 expression and overall survival (OS) in advanced non-small cell lung cancer (aNSCLC). (15th December 2019) - Staib, J; Sudarsanam, S; Byfield, S Dacosta; Kennedy, C; Weiss, L
Abstract: Background: Clinical trials show favorable OS for patients (pts) with incident aNSCLC and programmed death ligand 1 (PD-L1) expression treated with PD-L1 immune checkpoint inhibitor (ICI) pembrolizumab (PEM) or PEM-chemotherapy compared to no ICI. We use real world data to examine OS in pts with PEM-based regimens vs NoICI as initial aNSCLC treatment by PD-L1 expression. Methods: This retrospective study used de-identified administrative claims, including month of death (MoD) from regular operations, spanning 1/2017-12/2018 from a large, national US insurer. Claims were linked with biomarker test data from a CLIA-certified cancer diagnostics lab. During 2018, Medicare Advantage pts having ≥1 claim with diagnosis (dx) of lung cancer (ICD-10 C34), advanced disease (C77-C79), a PD-L1 test (CPT 88360) and test result, Tumor Proportion Score (TPS), were included. Pts were newly diagnosed (no C34 in 2017) and continuously enrolled in 2017 & 2018 or until death in 2018. Cohorts were based on initial therapy as PEM-based or NoICI and TPS result. Pts were followed from dx to MoD or 12/2018. OS was MoD, minus month of dx; otherwise censored at 12/2018. Multivariable Cox proportional hazard regressions compared OS across cohorts. Results: 457 pts met study criteria: 126 PEM-based and 331 NoICI. Median age was 76 years in both cohorts. PEM-based had more males (63% vs 51%; p = 0.02) Median months followed was 6 (PEM-based) and 4 (NoICI). For PEM-based, 23 (18%) had TPS 0, 36 (29%) had TPS 1- 49 and 67 (53%) had TPS 50+. For NoICI, 118 (36%) had TPS 0, 120 (36%) had TPS 1- 49, and 93 (28%) had TPS 50+. 20% (n = 25) of PEM-based and 31% (n = 104) of NoICI died during the study period. Mortality hazard ratios for PEM-based vs NoICI by TPS score were: TPS 0, 0.46 (CI 95% 0.16 – 1.30); TPS 1 to 49, 0.73 (CI 95% 0.35 – 1.52); and TPS 50+, 0.35 (CI 95% 0.18 – 0.68). OS was more favorable for the PEM-based cohort for all TPS groups, though only TPS 50+ was significant. Conclusion: This study used administrative claims and lab test data allowing examination of effectiveness of PEM-based vs. NoICI therapy for aNSCLC. As in clinical trials, this analysis suggests OS benefit for PEM-based vs NoICI. Further analysis with longer follow-up will better assess OS benefit by TPS score. Legal entity responsible for the study: UnitedHealth Group. Funding: Has not received any funding. Disclosure: J. Staib: Shareholder / Stockholder / Stock options, Full / Part-time employment: UnitedHealth Group; Shareholder / Stockholder / Stock options: Bristol Myers Squibb; Shareholder / Stockholder / Stock options: Merck; Shareholder / Stockholder / Stock options: Natera; Shareholder / Stockholder / Stock options: NeoGenomics. S. Sudarsanam: Shareholder / Stockholder / Stock options, Full / Part-time employment: NeoGenomics Laboratories. S. Dacosta Byfield: Shareholder / Stockholder / Stock options, Full / Part-time employment: UnitedHealth Group. C. Kennedy: Shareholder / Stockholder / Stock options, Full / Part-time employment: UnitedHealth Group. L. Weiss: Shareholder / Stockholder / Stock options, Full / Part-time employment: NeoGenomics Laboratories.